EFFECT OF MANGOSTEEN EXTRACT ON NEUROINFLAMMATION IN RAT MODEL OF ACUTE TRAUMATIC BRAIN INJURY - PANGIHUTAN SIAHAAN, ANDRE MAROLOP; LUMBANRAJA, SARMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Traumatic brain injury (TBI) is one of the major health problems regarding morbidity and mortality, especially in productive ages. Following primary injury, there is a secondary insult, resulting in oxidative stress, neuroinflammation, and cell death. Mangosteen is a powerful natural antioxidant and anti-inflammation that also has neuroprotective property. The aim of this study was to explore the effect of mangosteen extract (ME)on neuroinflammation following TBI. Methods: A total of 30 Sprague-Dawley rats were randomized into three treatments group, i.e., sham-operated controls, closed head injury (CHI), and treatment group. In the treatment group, we gave ME once daily every day after CHI for 7 days. As oxidative process marker, we investigated malondialdehyde (MDA) expression. As neuroinflammation marker, we investigated glial fibrillary acidic protein (GFAP) and CD-68. Results: TBI increased the expression of GFAP and CD-68, but not MDA. There was significant GFAP expression difference between treatment group and CHI group. Regarding the expression of CD-68 and MDA, there was no significant difference between treatment and CHI group. Conclusion: Mangosteen extract supplementation decreased GFAP expression significantly after TBI.